The Power of Smartphone Use in Enhancing Psychological Well-Being of University Students - Oyoo, Eliud; Zainabu, Odindo; Onyango, Tom (African Journal of Education,Science and Technology (AJEST), 2024)
Smartphones are considered a necessity in students’ campus life globally. Several research findings show that students use them for their daily communication, social networking, entertainment, and research, among many others as the main uses. However, there is scanty documentation on its use as an avenue for psychological well-being. The objective of this research was to assess the awareness level of the usability of smartphones for the psychological well-being of university students. This study adopted the cross-sectional survey research design and mixed methods approach. A random sample size of 365 university students of years 2 and 3 from the 4 schools of Rongo University and 10 student counselors of Rongo University were involved in data collection. Quantitative data was collected by use of questionnaires while qualitative data was collected by use of interview guide. Quantitative data was analyzed descriptively into percentages, means, and standard deviations, while the inferential statistical analysis used was t-test and correlation. The analyzed findings were presented in the form of tables. The qualitative data was analyzed through a thematic approach and then triangulated with the quantitative data findings in the discussion. The study established that there is a statistically significant moderate positive influence (r=.391) of the awareness level of usability of smartphones on the psychological well-being of university students (p = .000) at an alpha value of .05. The research findings concluded that awareness level of usability of smartphones can moderately and positively influence the psychological well-being of university students. Thus the study recommended that universities should focus on awareness creation of the usability of smartphones in their students to enhance their psychological well-being.